2014
DOI: 10.1002/pc.23171
|View full text |Cite
|
Sign up to set email alerts
|

Optically transparent polycarbonate/clay nanocomposites with improved performance using phosphonium modified organoclay: Preparation and characterizations

Abstract: The present work focuses on the morphology and properties of polycarbonate (PC)/clay nanocomposites prepared through melt blending and solution blending at two different loadings of organoclay (0.5 and 1 phr). The oraganoclay was prepared by incorporating thermally 2-oxopropyl triphenyl phosphonium ion (OTPP) into the clay gallery with an intention to preserve the optical transparency of PC in the PC/clay nanocomposites. An increase in gallery height from 1.24 to 1.86 nm along with the extraordinary thermal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…18,19 Based on this cognition, massive effective ame retardants have been developed and applied in ame retarding PC materials, including halogencontaining, 20 sulphonate-containing, 21,22 organosilicon-containing, 23 phosphorus-containing compounds, 24 inorganic additives, 25 and nanomaterials. 26,27 Recently, as a promising intermediate in developing novel halogen-free ame retardants, 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide (DOPO) have been frequently used to synthesize effective and efficient phosphaphenanthrene-containing ame retardant additives for various polymer materials. [28][29][30][31][32][33] And some similar works have also suggested that the addition of phosphaphenanthrenecontaining additive indeed improved the ame retardancy of PC materials effectively.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Based on this cognition, massive effective ame retardants have been developed and applied in ame retarding PC materials, including halogencontaining, 20 sulphonate-containing, 21,22 organosilicon-containing, 23 phosphorus-containing compounds, 24 inorganic additives, 25 and nanomaterials. 26,27 Recently, as a promising intermediate in developing novel halogen-free ame retardants, 9,10-dihydro-9-oxa-10-phosphaphenanthrene 10-oxide (DOPO) have been frequently used to synthesize effective and efficient phosphaphenanthrene-containing ame retardant additives for various polymer materials. [28][29][30][31][32][33] And some similar works have also suggested that the addition of phosphaphenanthrenecontaining additive indeed improved the ame retardancy of PC materials effectively.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 2, the dispersions in water at room temperature of pristine Na + -MMT and of modified Na + -MMT/MMA before (Figure 2 In these images, we can observe that the pristine Na + -MMT is highly hydrophilic and disperses well in water after agitation. This is due to the high content of Na + cations present in the clay which have been hydrated (solvated with water, Figure 2(b)) [27,28,45]. For Na + -MMT/MMA, with different time of plasma modification, it is observed that they stay on the surface of the water before and after agitation, which identifies their hydrophobic property; the presence of the polymer on the surface of Na + -MMT indicates a difference in between the coating of PMMA ( = 9.25) and H 2 O ( = 23.5), which avoids the diffusion of water between the sheets and consequently their interaction with the sodium ions.…”
Section: Characterization Of Nanoclaymentioning
confidence: 99%
“…In this stage, there is in situ polymerization, solution mixing, and melt blending as the main techniques of nanocomposite preparation which have revealed favorable levels of dispersion [23,24]. Particularly polymer/clay composites are generally divided in three types: conventional composite materials, where the clay acts as a normal reinforcement material [23,25], intercalated nanocomposites, where a small quantity of polymer moves into the gallery spaces of the clay [26,27], and exfoliated nanocomposites, where the sheets of clay are completely dispersed in a polymer matrix [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PC/clay nanocomposites have been prepared by in situ intercalative polymerization and polymer melt intercalation using alkyl ammonium or phosphonium modified clay. This ambiguity may seem paradoxical about the effect of clay on thermal stability of PC nanocomposites.…”
Section: Introductionmentioning
confidence: 99%